Perancangan Sistem Informasi Monitoring Status Gizi Program MBG Berbasis Web di Yayasan Al Rusyda - Said Muhammad Rifki; Sholihin; Adi Rahmat; Bagus Nur Wahit (CV. Multi Kreasi Media, 2026)
The development of information technology has significantly impacted data management, including monitoring and evaluating nutritional status. At Yayasan Al Rusyda, the monitoring process for the Free Nutritious Meal Program (MBG) was still manual, causing delays in data processing, recording errors, and difficulties in report generation. This study aims to develop a website-based information system for monitoring and evaluating nutritional status using the Laravel framework and Laragon database. The system development method used is the Waterfall method, comprising requirement analysis, system design, implementation, and testing stages. The developed system is capable of assisting participant data management, nutritional status recording, Body Mass Index (BMI) calculation, and report generation more quickly and accurately. The testing results using the Blackbox Testing method indicates that all system features function properly according to user requirements. This system is expected to improve the effectiveness, efficiency, and structure of nutritional status monitoring and evaluation processes.